Effect of Gamma Irradiation (Cesium-137) on the Properties of Chemical Functional Groups from Collagen Extraction of Snakehead Fish Scales (Channa striata) - Ferdianti, Andi Tasya; Fuadi, Nurul; Fitriyanti, Fitriyanti; Abidin, Kurniati; Jumardin, Jumardin; Isradiati, Dwi Febri (Lambung Mangkurat University Press, 2024)
This study aims to determine the absorption spectrum of the functional groups of snakehead fish scale collagen before irradiation and the effect of the dose of Cesium-137 irradiation on the functional groups in snakehead fish scale collagen. The extraction method used is acid extraction. Measurement of the absorption spectrum of collagen samples from snakehead fish scales using an FTIR spectrophotometer. Samples were irradiated using doses of 10 mGy, 30 mGy and 50 mGy. The results of the functional group values before irradiation produce amide A, amide I, amide II and amide III which fill the absorption area of the functional group. The results of the functional group values produced after irradiation for a dose of 10 mGy produced amide I, amide II and amide III which filled the absorption area. Amide A and amide B do not fill the absorption region at a dose of 10 mGy. Doses of 30 mGy and 50 mGy produced amide A, amide I, amide II and amide III which filled the absorption area. Amide B did not fill the absorption area at doses of 30 mGy and 50 mGy. Amide groups that are not detected or do not meet standard collagen functional group standards can be caused by the chemical composition of the fish scale extraction process.